Implementasi Green Marketing Mix dalam Upaya Meningkatkan Keunggulan Kompetitif - Ibrahim, Darmawansah (Jurnal Ilmiah Manajemen & Kewirausahaan, 2024)
This study aims to analyze the implementation of the green marketing mix and its impact on the competitive advantage of companies. The green marketing mix includes product, price, promotion, and distribution strategies that emphasize environmentally friendly practices and sustainability. The application of this strategy is believed to enhance corporate reputation, consumer satisfaction, and product differentiation in an increasingly environmentally conscious market. The study uses a quantitative approach with a survey method, collecting data through questionnaires distributed to consumers and business practitioners who implement the green marketing mix. The results indicate that the implementation of the green marketing mix has a positive effect on competitive advantage. The application of environmentally friendly marketing strategies allows companies to strengthen brand image, increase consumer loyalty, and create added value that differentiates the company from its competitors.